Finite element modelling and analysis of certain "scissors-type" mechanism - Lim, Lionel Li Rong (Nanyang Technological University, 2022)
Mechanisms are commonly used to convert input forces into desired output forces. Many different mechanisms exist in engineering. One of such mechanisms is the scissors mechanism. Common real-world applications of the scissors mechanisms include scissors lifts as well as mobile bridges. Most practical scissors mechanisms are rectilinear in nature (involving translational motion). However, curvilinear scissors mechanisms are quite rare. Hence, the focus of this project is to conduct finite element analysis of curvilinear scissors mechanisms so as to study its deformation behaviour, and natural frequencies and node shapes. For the finite element analysis, ANSYS Mechanical APDL (Student Version) is used. Firstly, using MATLAB, a visualisation of the trajectory of the curvilinear scissors mechanisms for the modelling of the mechanism is achieved. Next, a geometric model of the structure is constructed in ANSYS and meshed in appropriate finite element. Static structural and modal analysis are carried out. Two different curvilinear geometries (quadrant and semi-circular) as well as two different applications (robot arm and overhead shelter) are studied. The static analysis reveals that the maximum stress is developed in members in the vicinity of the support end. The maximum deflection is observed at the members in the vicinity of the applied load. The modal analysis reveals that the structure generally vibrates in 2 modes, viz., axial and bending modes.